The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1149/1.1579033
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure and Character of the PVDF-g-PSSA Membrane Prepared by Solution Grafting

Abstract: A new method based on a solution-grafting technique was used to prepare poly(vinylidene fluoride) grafted polystyrene sulfonated acid (PVDF-g-PSSA) proton exchange membrane. Polystyrene is easily grafted into PVDF, which has been treated in KOH solution. There is a linear relationship between the degree of grafting and the treatment time in KOH solution. Fourier transform infrared spectroscopy and differential scanning calorimetry were used to characterize the changes of the membrane’s microstructure after gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 15 publications
2
32
1
Order By: Relevance
“…Finally, the membrane was washed with deionized water to remove the remaining sulfuric acid. 8 2.2. Membrane Characterization.…”
Section: Membrane Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the membrane was washed with deionized water to remove the remaining sulfuric acid. 8 2.2. Membrane Characterization.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…7 In our laboratory, we have studied a solution-grafting technique for the preparation of the PVDF-g-PSSA membrane. 8 Some properties of the PVDF-g-PSSA membranes produced by the same method were investigated in this paper. The membranes were measured for their ion exchange capacity (IEC), proton conductivity, water uptake, and vanadium ion permeability in comparison with the Nafion 117 membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The change of methanol concentration with time in reservoir B was measured using a capillary gas chromatographic instrument (HP5890). The methanol permeability was calculated using the following equation, which has already been applied elsewhere [22,23]:…”
Section: Methanol Permeabilitymentioning
confidence: 99%
“…It comprises both an amorphous and crystalline phase where an amorphous phase of the polymer support higher ionic conduction and crystalline phase assists to enhance the mechanical strength for the polymer electrolytes [5]. P(VdFco-HFP) based polymer electrolyte is one of the most commonly commercialized plastic lithium ion batteries (PLiON) by Telcordia Technologies (formerly Bellcore) since Gozdz et al found the preparation process of porous membrane [6][7][8][9]. However, in the process di-butyl phthalate (DBP) extraction step is inconvenient since it increases the cost of the preparation.…”
Section: Introductionmentioning
confidence: 99%